Impacts of Acidic Seawater on Early Developmental Stages of Fucus gardneri at Burrard Inlet, British Columbia - Schiltroth, Braeden W. J.; Ohori, Kyle T.; Bisgrove, Sherryl R. (Frontiers in Marine Science, 2019)
Increases in stressors associated with climate change such as ocean acidification and warming temperatures pose a serious threat to intertidal ecosystems. Of crucial importance are the effects on foundational species, such as fucoid algae, a critical component of rocky intertidal shorelines around the world. The impact of climate change on adult fronds of fucoid algae has been documented but effects on early developmental stages is not as well understood. In particular, ocean acidification stands to impact these stages because zygotes and embryos are known to maintain internal pH and develop a cytosolic pH gradient during development. To assess the effects of seawater acidification on early development, zygotes were exposed to conditions that approximate current global averages and extend beyond future projections. Exposure to acidic seawater had significant effects on embryonic growth. Specifically, rhizoid elongation, which occurs by a process known as tip growth, was significantly reduced with each 0.5 unit drop in pH. Even a moderate decrease in pH from 8.0 to 7.5, which is similar to levels observed in the field, was associated with a nearly 20% reduction in rhizoid growth rate. Under more extreme conditions, at pH 6, rhizoid growth rates were reduced by 64% in comparison to embryos exposed to seawater at pH 8.0. On the other hand, acidic seawater had no effect on earlier processes; zygotes became multicellular embryos with well-formed rhizoids on a similar time course within the first 24 hours of development, even when exposed to pH 6, an extreme pH well below what is expected in the future. This suggests that zygotes can maintain an internal pH that allows germination and cell division to occur. Tip growth however, depends on the maintenance of an internal pH gradient. It is therefore possible that disruptions to this gradient could account for the observed reductions in rhizoid elongation. Under acidic conditions proton influx into the cell becomes energetically more favorable than at pH 8, and expulsion would be more difficult. This could disrupt the cytosolic pH gradient and in turn affect rhizoid growth.